2023
DOI: 10.1021/acs.jctc.3c00033
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Theoretical Study on Four Typical Intramolecular Hydrogen Shift Reactions of Peroxy Radicals: Multireference Character, Recommended Model Chemistry, and Kinetics

Abstract: Intramolecular hydrogen shift reactions in peroxy radicals (RO 2 • → • QOOH) play key roles in the low-temperature combustion and in the atmospheric chemistry. In the present study, we found that a mild-to-moderate multireference character of a potential energy surface (PES) is widely present in four typical hydrogen shift reactions of peroxy radicals (RO 2 • , R = ethyl, vinyl, formyl methyl, and acetyl) by a systematic assessment based on the T 1 diagnostic, %TAE diagnostic, M diagnostic, and contribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 162 publications
0
3
1
Order By: Relevance
“…A recent study on four intramolecular H-shift reactions of peroxy radicals also found MN15L and MN12L to perform better compared to other DFT methods. 77 However, in our study, MN12L shows a large MAD of about 6 kcal mol −1 without dressed-atom corrections. For an overall performance considering both the reaction energies and reaction barriers, G4 has the lowest error of 0.88 kcal mol −1 among cWFTs.…”
Section: Resultscontrasting
confidence: 64%
See 2 more Smart Citations
“…A recent study on four intramolecular H-shift reactions of peroxy radicals also found MN15L and MN12L to perform better compared to other DFT methods. 77 However, in our study, MN12L shows a large MAD of about 6 kcal mol −1 without dressed-atom corrections. For an overall performance considering both the reaction energies and reaction barriers, G4 has the lowest error of 0.88 kcal mol −1 among cWFTs.…”
Section: Resultscontrasting
confidence: 64%
“…This journal is © the Owner Societies 2023 combination with the VDZ-F12 basis set, which has been extensively used to study species involved in low-temperature combustion. 20,[77][78][79] The F12 method is an explicitly correlated version of the canonical CCSD(T) method involving a factor that depends on the explicit two-electron distance, r 12 .…”
Section: Pccp Papermentioning
confidence: 99%
See 1 more Smart Citation
“…The Gaussian 09 set of programs package was used for all of the calculations. The geometries of reactants, transition states, and products were fully optimized using density functional theory (DFT) method at the level of Becke3LYP (B3LYP) with a 6-31+G (d, p) basis set. Vibrational frequency analysis was used to confirm that the reactant or product has no imaginary frequency, while the transition state exhibits only one imaginary frequency. Intrinsic reaction coordinate (IRC) was calculated to verify that transition states can link substrates and products.…”
Section: Methodsmentioning
confidence: 99%